Development of abdominal compartment syndrome secondary to tumor lysis in an infant with disseminated stage 4 neuroblastoma despite decompressive laparotomy - Grigoriy V. Klimovich; Carmen T. Ramos-Irizarry; Gavin A. Falk; Tara Loux (Elsevier, 2016)
A 7-week-old girl presented with disseminated stage 4 neuroblastoma complicated with massive hepatomegaly and signs of liver failure. She underwent wedge liver biopsy and decompressive laparotomy with GORE-TEX® patch placement prior to the administration of chemotherapy. Her fluid losses during chemotherapy were so severe that her GORE-TEX® patch became tense and filled with ascites resulting in abdominal compartment syndrome (ACS). A negative pressure dressing system was applied after opening the patch to assist in the quantification of the fluid losses and to allow decompression. Unfortunately, in spite of favorable histology, the patient failed to adequately respond to chemotherapy resulting in persistent hepatomegaly. Soon after, she developed respiratory, renal insufficiency and disseminated intravascular coagulation, leading to her death 12 days after the initiation of treatment.